HUBUNGAN PENGETAHUAN TERAPI DIET GINJAL DENGAN ASUPAN ENERGI, PROTEIN, FOSFOR, KALIUM, DAN NATRIUM PADA PASIEN PENYAKIT GINJAL KRONIK DENGAN HEMODIALISA DI RSU TANGERANG SELATAN - Septi Nur Hidayah (2021)
Disorders of nutritional status can occur in patients with chronic kidney disease on hemodialysis because it can cause loss of nutrients that are still needed by the body such as protein, glucose, and water-soluble vitamins. Incidence of deficiency or excess of one or more micronutrient substances can also occur in hemodialysis patients. Therefore, one of the big problems that can contribute to the hemodialysis process is compliance with the patient's food intake. One of the factors that can affect dietary compliance is knowledge about kidney diet therapy owned by patients with chronic kidney disease on hemodialysis which will affect healthy attitudes and behavior in carrying out diet therapy and hemodialysis correctly. This study was conducted to determine the relationship between knowledge of renal diet therapy with intake of energy, protein, phosphorus, potassium, and sodium in patients with chronic kidney disease on hemodialysis. This research is an observational analytic study with a cross sectional approach. The research subjects were patients with chronic kidney disease who underwent routine hemodialysis. The number of subjects was 33 patients, taken by purposive sampling. Data on name, age, education level, duration of hemodialysis, history of nutritional counseling, and knowledge of renal diet therapy were obtained from questionnaires and patient medical records. Meanwhile, data on energy, protein, phosphorus, potassium, and sodium intake were measured by SQ-FFQ. There was a significant relationship between knowledge of renal diet therapy and intake of energy, protein, and potassium (p<0.05; p = 0.000). There was no significant relationship between knowledge of renal diet therapy with intake of phosphorus (p < 0.05; p = 0.772) and sodium (p <0.05; p = 0.423).